Credit Rating Changes and the Bond Market – the Impact of Economic Development - Patrycja Chodnica-Jaworska (Problemy Zarządzania, 2019)
The aim of the paper is to examine the impact of credit rating changes of a country on bond yields, taking into account this country’s level of economic development. The following hypothesis has been formulated following a literature review: Bond yields react more strongly to credit rating changes in developed economies. The impact is greatest in the case of credit rating downgrades both in developed and developing economies; in developing economies, both upgrades and downgrades affect bond yields. Event study methodology has been applied to analyse Thomson Reuters’s database of 225 countries, published daily between 1980 and 2016. Research results may be used to analyse the influence of information published by lesser agencies on investors’ decisions. The analysis encompasses the impact of credit rating changes published by smaller agencies, which has yet to be subject to scholarly investigation.